Transition to adulthood and recession: a qualitative study. (13th September 2016) - Di Blasi, Maria; Tosto, Crispino; Marfia, Alessandro; Cavani, Paola; Giordano, Cecilia
ABSTRACT: While the transition to adulthood has been broadly examined, less is known about the impact of economic recession on the well-being and psychosocial functioning of young people. The present study used qualitative interviews with 12 college students to understand their experience. Consensual qualitative research was used to analyse data and develop core themes around young people's experiences. Interviews focused on how young people perceived the impact of the economic recession on their social context and on emotional, behavioural, and interpersonal dimensions. Although students showed a proactive attitude in dealing with the crisis, findings highlighted a negative impact on psychological functioning characterized by feelings of instability and helplessness and by difficulties in planning for the future. Other general themes emerged, including disengagement from community participation expressed by feelings of isolation, lack of interest, and distrust. Directions for future research and implications for practice are discussed.